RESISTÊNCIA A ANTIMICROBIANOS EM CEPAS DE E. COLI ISOLADAS DAS ÁGUAS DO ARROIO ESPINHO NO PRIMEIRO SEMESTRE DE 2007 - BELLINASO, MARIA D. L.; ALMEIDA, MARIS L.; OLIVEIRA, ROSEMERI M. D. (Salão do Conhecimento, 2013)
Resumo